Effect of planting density and micronutrient application on growth, physiological parameters and yield of rice (Oryza sativa) - RAJPUT, PRADEEP; SINGH, ADESH; KUMAR, MUKESH; VIVEK; YADAV, R B; SHAHI, U P (The Indian Journal of Agricultural Sciences, 2023)
The field experiments were conducted during the rainy (kharif) seasons of 2019 and 2020 at crop research centre (CRC) of Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, Uttar Pradesh to study the effect of seedling density and micronutrient application on growth, physiological parameters and yield of basmati rice (Oryza sativa L). Three planting densities, viz. 1 seedling per hill, 2 seedlings per hill and 3 seedlings per hill and 5 foliar application of micronutrient [MN0-control; MN1, B @0.04% and Fe @0.1% at maximum tillering (MT) stage; MN2, B @0.04% and Fe @0.1% at panicle initiation (PI) stage; MN3, Fe @0.1% at maximum tillering stage (MT) and B @0.04% at panicle initiation (PI) stage and MN4, B @0.04% and Fe @0.1% at maximum tillering (MT) and panicle initiation (PI) stages] were tested in a split plot design, keeping as main plots and sub plots, respectively with 3 replications. The growth, physiological traits and yield of basmati rice were significantly influenced by varying planting density and micronutrients application through leaves, as indicated by the outcomes of the experiments. Growth and physiological parameters such as dry matter accumulation, leaf area index, plant height, chlorophyll content, crop growth rate and relative growth rate increased through the application of boron and iron, being highest in foliar spray of 0.04% B and 0.1% Fe at both the stages (MT and PI). Of the different seedling densities, 3 seedlings per hill resulted in significantly higher grain yield (5.0 and 5.1 t/ha) during 1st and 2nd year, respectively. In both the years, the highest grain and straw yield were observed by using 3 seedlings per hill along with a foliar application of 0.04% B and 0.1% Fe during the MT and PI stages.